On state instability of the bi-stable flow past a notchback bluff body. (25th January 2022) - He, Kan; Minelli, Guglielmo; Su, Xinchao; Gao, Guangjun; Krajnović, Siniša
Abstract: Abstract : The wake of a notchback Ahmed body presenting a bi-stable nature is investigated by performing wind tunnel experiments and large-eddy simulations. Attention is confined to the Reynolds number ( $Re$ ) influence on the wake state instability within $5× 10^{4}≤ Re ≤ 25× 10^{4}$ . Experimental observations suggest a wake bi-stability with low-frequency switches under low $Re$ . The wake becomes 'tri-stable' with the increase of $Re$ with the introduction of a new symmetric state. The higher presence of the symmetric state can be considered as a symmetrization of the wake bi-stability with an increasing $Re$ . The wake symmetry under high $Re$ attributed to the highly frequent switches of the wake is extremely sensitive to small yaw angles, showing the feature of bi-stable flows. The wake asymmetry is confirmed in numerical simulations with both low and high $Re$ . The wake asymmetries are indicated by the wake separation, the reattachment and the wake dynamics identified by the proper orthogonal decomposition. However, the turbulence level is found to be significantly higher with a higher $Re$ . This leads to a higher possibility to break the asymmetric state, resulting in highly frequent switches showing symmetry.